Cold water recovery reduces anaerobic performance - Crowe, M. J.; O'Connor, D.; Rudd, D. (International Journal of Sports Medicine, 2007)
This study investigated the effects of cold water immersion on recovery from anaerobic cycling. Seventeen (13 male, 4 female) active subjects underwent a crossover, randomised design involving two testing sessions 2 - 6 d apart. Testing involved two 30-s maximal cycling efforts separated by a one-hour recovery period of 10-min cycling warm-down followed by either passive rest or 15-min cold water immersion (13 - 14 °C) with passive rest. Peak power, total work and postexercise blood lactate were significantly reduced following cold water immersion compared to the first exercise test and the control condition. These variables did not differ significantly between the control tests. Peak exercise heart rate was significantly lower after cold water immersion compared to the control. Time to peak power, rating of perceived exertion, and blood pH were not affected by cold water immersion compared to the control. Core temperature rose significantly (0.3 °C) during ice bath immersion but a similar increase also occurred in the control condition. Therefore, cold water immersion caused a significant decrease in sprint cycling performance with one-hour recovery between tests.